Analisis Motivasi Kerja pada KPRI Koperasi Pegawai Kesehatan Sumedang - Wulan Ariani Damayanti (SINTESA, 2022)
Analysis of Work Motivation at KPRI Koperasi Sumedang Health Employee Sumedang Health Employee Cooperative is one of the cooperatives in Sumedang that has decreased members compared to other cooperatives. The decrease in cooperative members shows that the motivation of health workers to become cooperative members is still low. Based on this, the purpose of this study was to determine the implementation and efforts to increase work motivation in the Sumedang Health Employee Cooperative. This research method uses a qualitative research method approach. Data collection techniques carried out through interviews, observation and documentation. The sampling technique was carried out with a porposive sampling technique with work motivation as the research variable. The sample or research informants are cooperative employees. The research data were analyzed using the Miles and Huberman model with steps including data reduction, data presentation, and drawing conclusions. Work motivation variables are analyzed through Maslow's theoretical approach including physiological needs, security, social, self-esteem and recognition, in actualization. The results showed that the implementation of work motivation on KPRI Koperasi Sumedang Health Employee Cooperative was not going well or had not been maximally implemented. Then the efforts to increase work motivation in KPRI Koperasi Sumedang Health Employee Cooperative, namely as follows: pay more attention to motivation in the form of rewards per division, so as not to cause social jealousy among employees, more intense in providing psychological motivation to employees, improvement and renewal of motivation to employees with adjustments, because with the existence of good and appropriate employee motivation, work improvement will be better